2018
DOI: 10.1021/acs.jpca.8b10680
|View full text |Cite
|
Sign up to set email alerts
|

AIR-Chem: Authentic Intelligent Robotics for Chemistry

Abstract: The new era with prosperous artificial intelligence (AI) and robotics technology is reshaping the materials discovery process in a more radical fashion. Here we present authentic intelligent robotics for chemistry (AIR-Chem), integrated with technological innovations in the AI and robotics fields, functionalized with modules including gradient descent-based optimization frameworks, multiple external field modulations, a real-time computer vision (CV) system, and automated guided vehicle (AGV) parts. AIR-Chem i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 26 publications
0
40
0
Order By: Relevance
“…Previous work reported that the additional injection during the growth could significantly improve the size distribution . Here we apply MAOS by variant injection time interval τ and the times of the injection operation η, and we keep the total injection amount η* c η constant for different η value .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work reported that the additional injection during the growth could significantly improve the size distribution . Here we apply MAOS by variant injection time interval τ and the times of the injection operation η, and we keep the total injection amount η* c η constant for different η value .…”
Section: Resultsmentioning
confidence: 99%
“…The CV analyzer based on OpenCV library was applied to extract red, green and blue (RGB) information from video streams captured by the in‐built camera, and then mapped it into the average particle size 〈 D RGB 〉 or 〈 D 〉 From a well‐benchmarked machine learning scheme. Details of the analyzing algorithms were described in our previous work . The spectrum analyzer is used to extract the demand optical information from spectrum files generated by spectrometer software.…”
Section: System Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…), and perform in situ analysis. [6][7][8][9] When combined with smart machinery and a clear set of instructions, computer vision can also be used to drive control decisions.…”
Section: Introductionmentioning
confidence: 99%
“…The approach of iterating between automated experimentation and machine learning-based experiment planning has resulted in early successes in addressing high-dimensional problems in experimental physics 21 , chemistry 22 , life-sciences 23 , and recently starting to be implemented in the materials sciences [24][25][26][27] . To get insight into the variability of the optical band gap and photoluminescent properties across the compositional series, we will adopt the approach based on the multivariate statistical analysis.…”
mentioning
confidence: 99%